2018
DOI: 10.1002/adhm.201701324
|View full text |Cite
|
Sign up to set email alerts
|

Integrin Clustering Matters: A Review of Biomaterials Functionalized with Multivalent Integrin‐Binding Ligands to Improve Cell Adhesion, Migration, Differentiation, Angiogenesis, and Biomedical Device Integration

Abstract: Material systems that exhibit tailored interactions with cells are a cornerstone of biomaterial and tissue engineering technologies. One method of achieving these tailored interactions is to biofunctionalize materials with peptide ligands that bind integrin receptors present on the cell surface. However, cell biology research has illustrated that both integrin binding and integrin clustering are required to achieve a full adhesion response. This biophysical knowledge has motivated researchers to develop materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 137 publications
(290 reference statements)
0
84
0
1
Order By: Relevance
“…All the above studies measured cell size by image analysis of micrographs taken of adherent MSCs during culture. It is well established that variables such as substrate stiffness, ligand presentation, ligand density, and cell motility all impact on the apparent size and shape of adherent cells,, but these confounding factors were not taken into account in these previous studies. To minimize these confounding factors, we used two methods of assessing comparative MSC size for suspended cells.…”
Section: Discussionmentioning
confidence: 99%
“…All the above studies measured cell size by image analysis of micrographs taken of adherent MSCs during culture. It is well established that variables such as substrate stiffness, ligand presentation, ligand density, and cell motility all impact on the apparent size and shape of adherent cells,, but these confounding factors were not taken into account in these previous studies. To minimize these confounding factors, we used two methods of assessing comparative MSC size for suspended cells.…”
Section: Discussionmentioning
confidence: 99%
“…Random positioning of peptide functionalised DNA origami demonstrated that a minimum of 12 peptides per DNA origami (~120 36 ligands/µm 2 ) were required to initiate cardiomyocyte ± adhesion and spreading. However, random positioning of DNA origami provides no control over ligand geometry above the level of individual origami (~ 85 nm 2 ) and offers limited information on global and local clustering dynamics, which are key for cell adhesion and spreading 5,21 . To investigate this, DNA origami functionalised with 0, 6 or 12 cRGDfC peptides were bound to EBL nanopatterned substrates at 200 nm and 300 nm intervals ( Figure 5), and this allowed us to further investigate the role of cluster spacing, due to the differences in receptor clustering behaviour between cardiomyocytes and fibroblasts.…”
Section: Nanoscale Control Of Global and Local Ligand Clustering Dynamentioning
confidence: 99%
“…The ECM components serve as anchoring points for the cells, but binding of integrins and other cell surface receptors also induce cellular signalling cascades which regulate fundamental processes from cell growth, to differentiation, motility or cell death 1 . The contact interface between the ECM and cell-binding domains, depends on the receptors' nanoscale spatial organisation 2,3 and clustering [4][5][6][7] . Integrin-ECM interactions are also regulated by cellular (cytoskeletal) and extracellular forces (such as the passive stiffness of the ECM) that affect the stability of the bonds 1,[8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…), and through that play an active role in bone formation. 20 Currently, bioactive materials such as hydroxyapatite and collagen are used in bone tissue engineering to modify some of the polymer properties. Hydroxyapatite has properties such as bioactivity, biodegradability and osteo-inductivity that improve bone regeneration.…”
Section: Introductionmentioning
confidence: 99%